Sulphide oxidation linked to the reduction of nitrate and nitrite in Thiobacillus denitrificans - Aminuddin, M.; Nicholas, D. J. D. (Elsevier, 1973)
1. Whole cells of Thiobacillus denitrificans reduce nitrite to NO, N2O and N2 when sulphide is the electron donor.